Administrative professionals’ quality of life in educational institutions: a systematic review protocol - Matias Noll; Priscilla Rayanne e Silva Noll; Nicolli Godoi Pereira; Regina Márcia Ferreira Silva; Isabela Fernanda Rodrigues de Oliveira; Michele da Silva Valadão Fernandes; Woska Pires da Costa; Alberto de Vitta (BMJ Open)
Introduction Indicators of administrative professionals’ quality of life (QoL) in educational institutions are essential for planning improvements in their daily lives. QoL is a recurring topic in academic research, particularly in the healthcare sector. Therefore, this study aims to evaluate the perceptions of administrative professionals in educational institutions regarding their QoL and the implications of remote and in-person work. Additionally, we aim to compare the QoL before, during and after the COVID-19 pandemic.Methods and analysis Five electronic databases will be searched for this systematic review: CINAHL, LILACS, PubMed, Scopus and Web of Science. Original, peer-reviewed articles published in any language, without time limitations, will be included in this study. Two researchers will screen the articles and extract the data. The included articles will be evaluated for the quality of their evidence using Grading of Recommendations, Assessment, Development and Evaluations. The risk of bias will be assessed using the Critical Appraisal Skills Programme checklist and the Downs and Black scale. A third reviewer will resolve any discrepancies.Ethics and dissemination The systematic review results will be published in a peer-reviewed journal and presented at a relevant conference. The data will not include individual patient data; therefore, ethical approval is not required.PROSPERO registration number CRD42022365862.